High Performance Liquid Chromatography Standardisation of the Hydroalcoholic Extract of Phaseolus radiatus Beans Based on Vitexin Content - Dhoble, Leena R; Itankar, Prakash R (Indian Journal of Natural Products, 2022)
Aim: Our research work deals with chromatographic standardisation of the ‘smart crop’ mungbean or Phaseolus radiatus L. Wilczek using high performance liquid chromatography (HPLC) with respect to vitexin, in addition to pharmacognostic and phytochemical analysis. Materials and Methods: Pharmacognostic standardisation of the plant included macroscopy, powder microscopy, physicochemical parameters, preliminary phytochemical screening, heavy metal testing and microbial contamination studies. Further, ‘70% v/v hydro-ethanolic mother extract of Phaseolus radiatus’ (PR) was obtained by maceration. Quantitative estimations and antioxidant assay of PR was performed followed by qualitative thin layer chromatography (TLC). Lastly, PR was quantified by HPLC using vitexin as the marker compound. Results: The percent yield obtained for PR was found to be 45.6 % w/w. IC50 value of PR was found to be 38.96 μg/ml. The Rf value of PR obtained by TLC was calculated to be 0.78, complementary to the reported Rf of vitexin. Further, HPLC studies helped in the confirmation and quantification of vitexin. Conclusion: The study helped in successful development of quality testing parameters and achieve phytochemical standardisation of Phaseolus radiatus plant with respect to vitexin, a principle constituent of mungbean. From the results obtained by antioxidant assay, TLC and HPLC, vitexin may be attributed to be one of the phytoconstituents responsible for the significant antioxidant potential of mungbean which can become a marker for deciding the quality of mungbean to be used for preparation of Ayurvedic medicines.
Keywords: HPLC; Mungbean; Phaseolus radiatus; Quantification; Standardisation; Vitexin